Wings of Desire The mystery that is Swan Lake - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2003)
The mystery that is Swan Lake. At the most basic level Swan Lake is about male unreliability and romantic betrayal, about the man who dumps the good princess for the brazen bad girl. PALABRAS CLAVE: Swan Lake, Tchaikovsky, success.